Marie Curie : a psychobiography - Roets, Elmeret (Rhodes University, Faculty of Humanities, Department of Psychology, 2016)
While researchers debate the value of psychobiographical research, interest in this area is growing on a national and international basis. Every year, the number of psychobiographical studies at universities in South Africa is growing. Psychobiographical research is qualitative research that utilises psychological theory to explore and describe the lives of extraordinary individuals. The primary aim of this psychobiography was to examine the life of Marie Curie (1867"“1934) by employing developmental psychologist and psychoanalyst Erik Erikson's (1959) theory of psychosocial personality development. Marie Curie was chosen as the research subject because of the researcher's personal interest and the subject's prominence as a female scientist. She was a Polish-born and naturalised French scientist who conducted pioneering research on radioactivity. Marie Curie's ground-breaking discoveries changed the way scientists think about matter and energy and introduced a new era in medical knowledge and the treatment of disease. Her life exemplifies a love of science, commitment, and perseverance. Data were collected from several primary and secondary sources on Marie Curie's life. The researcher developed a data-collection and analysis matrix to facilitate the systematic collection of data and analysis according to Erikson's stage theory of psychosocial personality development. This psychobiography suggests that unresolved infantile and early childhood crises gave rise to personality traits that eventually contributed to Curie's extraordinariness. In the case of Curie, personality traits that are often regarded as atypical or malignant, ironically encouraged perseverance, creativity, and productivity. This study complements the psychobiographical studies done in South Africa on extraordinary individuals. It demonstrated the value of psychobiographical research as a teaching instrument, revealed the usefulness of Erikson's theory, and illustrated the uniqueness of individuals.
Keywords: Curie, Marie -- 1867-1934 -- Psychology; Women chemists -- Poland -- Biography; Scientists -- Biography